Effect of miR-98/IL-6/STAT3 on Autophagy and Apoptosis of Cardiac Stem Cells Under Hypoxic Conditions In vitro - Li, Xueyuan; Zhang, Yang; Zhang, Guangwei (Current Stem Cell Research & Therapy, 2025)
BackgroundThe heavy burden of cardiovascular diseases demands innovative therapeutic strategies dealing with cardiomyocyte loss. Cardiac Stem Cells (CSCs) are renewable cells in the myocardium with differentiation and endocrine functions. However, their functions are significantly inhibited in conditions of severe hypoxia or inflammation. The mechanism of hypoxia affecting CSCs is not clear. Interleukin-6 (IL-6) appears active in both hypoxic and inflammatory microenvironments. The aim of this study was to explore whether IL-6 is related to CSC apoptosis and autophagy under severe hypoxia.MethodsIn this study, rat CSCs were extracted by alternate digestion. The interaction of miR-98 and IL-6 mRNA was detected by the dual luciferase method, and qPCR was applied to confirm the effect of miR-98 on IL-6 expression. The effect of IL-6 on CSC apoptosis was measured by flow cytometry and the effect of IL-6 on CSC autophagy by transmission electron microscopy. The western blot method was applied to detect the effect of IL-6 on the expressions of proteins related to apoptosis and autophagy. ANOVA and Dunnett T3's test were employed in the statistical analysis. When p < 0.05, the difference was significant.ResultsUnder severe hypoxia conditions, IL-6 increased CSC apoptosis and decreased p-STAT3 expression significantly. CSC apoptosis increased significantly after inhibition of the STAT3 signaling pathway under severe hypoxia. IL-6 could also significantly inhibit CSCs’ autophagy and block their autophagy flow under severe hypoxic conditions. Meanwhile, it was confirmed that miR-98 had a binding site on IL-6 mRNA and miR-98 significantly inhibited IL-6 mRNA expression in CSCs under severe hypoxic conditions.ConclusionmiR-98/IL-6/STAT3 has been found to be involved in the regulation of CSCs’ apoptosis and autophagy under severe hypoxic conditions and there might be a mutual linkage between CSCs’ apoptosis and their autophagy.
Keywords: miR-98; STAT3